Sonication Assisted Callus Growth, Protein Content, and Plant Regeneration of Silybum marianum L. - Shifa M. Salih (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
Silybum marianum L. is considered one of the most extensively used medicinal plants worldwide due to its therapeutic benefits. While ultrasound waves were used to enhance the properties of numerous plant species. However, no study was investigated on applying ultrasonic waves to this particular plant. Therefore, the study amid to assess the impact of different exposure periods (0,10, 20, 25, 30, 35, and 40 minutes) of a frequency of 47.6 KHz on callus induction, protein content, and plant regeneration in S. marianum. The effect of ultrasonication was distinctive in accelerating callus induction of S. marianum, especially in short exposing periods (10 and 20 minutes). The percentage of callus formation reached 100%, 83.3% for cotyledons and stem respectively, when exposed to 20 minutes of ultrasound. Additionally, growth and total protein content were increased at 40 days and 80 days post- treatments. In contrast, long exposing periods (30, 35, and 40 minutes) had a negative impact on callus induction from all explants, as well as on callus growth and protein content. Moreover, ultrasonication stimulated one-step shoot regeneration during callus induction. The percentage of this phenomenon reached 100% for cotyledon at 10 and 20 minutes exposing period. This study confirmed the advantages of applying ultrasonic waves, particularly during shorter period to enhance the cultivation of S. marianum in vitro.